Advances in pretreatment technology for handling the palm oil mill effluent: Challenges and prospects. (January 2022) - Ratnasari, Anisa; Syafiuddin, Achmad; Boopathy, Raj; Malik, Sana; Aamer Mehmood, Muhammad; Amalia, Rizki; Dwi Prastyo, Dedy; Syamimi Zaidi, Nur
Graphical abstract: Highlights: Advances in pretreatment technologies for handling POME are reviewed. Current pretreatment technologies can handle POME but with certain limitations. The use of magnetic composite adsorbents is promising to treat POME. Future studies should focus on nitrogenous matter, oil, and grease removal in POME. Abstract: The palm oil mill effluent (POME) from palm milling oil activities is discharged into various water bodies which poses several environmental problems including turbidity, increases COD and BOD, adds oil and grease, increases total nitrogen, and other pollutants. Therefore, it requires effective treatment to remove the pollutants before disposal. The objective was to critically discuss the performance of POME pretreatments along with their limitations. To offer a coverage on the present less efficient technologies, the opportunities and challenges of advanced pretreatments that combine magnetic materials and natural composites as adsorbents are comprehensively reviewed here. Moreover, potential of various magnetic materials for POME pretreatment has been described. Several existing pretreatment methods such as physical pretreatments, chemical pretreatments, coagulation-flocculation, and adsorption can remove pollutant content from POME with certain limitations and the use of magnetic composite adsorbents can enhance the treatment efficiency.